CIVIL LIABILITY OF COMPANIES THAT COMMIT FOREST DESTRUCTION FROM THE PERSPECTIVE OF ENVIRONMENTAL LAW IN INDONESIA - Alya Amanda; Laura Yolanda Hutabarat; Fany Annisa Nst; Bambang Fitrianto (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study examines the civil liability of companies that damage forests from the perspective of Indonesian environmental law. The main focus of the study is to evaluate how effective the implementation of the principle of liability in the context of environmental protection, especially through strict liability mechanisms. This study uses a normative legal approach with secondary legal materials and primary legal materials as data sources. Data collection techniques are carried out through literature and documentation studies and qualitative analysis using a descriptive approach. The results of the study indicate that the implementation of strict liability can improve corporate accountability; however, to clarify the accountability mechanism and improve public access to justice, the legal system still needs to be changed.